Gender Equality and Tourism: Beyond Empowerment 2018
DOI: 10.1079/9781786394422.0046
|View full text |Cite
|
Sign up to set email alerts
|

Tourism as empowerment: women artisan's experiences in central Mexico.

Abstract: This chapter seeks to contribute to the debate on tourism as empowerment, through the exploration of the life stories of two urban women who work as producers and vendors of handicraft pottery catering to domestic and international visitors in the 'Magical Town' of Metepec, in central Mexico. The cases presented highlight how tourism can open productive and socializing opportunities for women, contributing to their economic and psychological empowerment. The life stories illustrate how women engage in negotiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Research on women empowerment from a human capital perspective reveals its positive impact on sustainable development. The findings demonstrate how women can redefine and negotiate their identities and roles while challenging societal norms that limit their potential (Suárez, 2018).…”
Section: Relationship Between Variables Of Women's Involvement In Sus...mentioning
confidence: 93%
“…Research on women empowerment from a human capital perspective reveals its positive impact on sustainable development. The findings demonstrate how women can redefine and negotiate their identities and roles while challenging societal norms that limit their potential (Suárez, 2018).…”
Section: Relationship Between Variables Of Women's Involvement In Sus...mentioning
confidence: 93%
“…often domestic spaces versus public tourism spaces).. Scholars have examined the ways in which rural tourism can contribute to produce changes in gender norms mainly by generating work opportunities for women (Lenao & Basupi, 2016;Smritee & Brijesh, 2017). However, the literature has also shown that the economic changes produced by tourism development are not always accompanied by broader socio-cultural transformations (Kimbu & Ngoasong, 2016;Tran & Walter, 2014;Vizcaino-Suárez, 2018). Due to these tensions, even though rural women tend to appreciate the positive aspects of tourism work, the nature of such work and the prevalent gender expectations and stereotypes generate emotions with different outcomes at the individual and the social level (Ratten & Dana, 2017;Tran & Walter, 2014;Tucker, 2007).…”
Section: Introductionmentioning
confidence: 99%